Coral snake bites in Brazilian Amazonia: Perpetrating species, epidemiology and clinical aspects. (February 2020) - Bisneto, Pedro Ferreira; Alcântara, João Arthur; Mendonça da Silva, Iran; de Almeida Gonçalves Sachett, Jacqueline; Bernarde, Paulo Sergio; Monteiro, Wuelton Marcelo; Kaefer, Igor Luis
Abstract: Coral snakes constitute a relatively diverse and little known group of venomous snakes. So far, data for this kind of snakebite in the Amazon region are based only on case reports. This study takes advantage of novel data from the Brazilian Health Ministry database from 2010 to 2015 and presents a review of the cases reported in the literature regarding the Amazonian biome both from Brazil and nearby countries. Thirty-four cases reported in the database were used in the study, representing 0.05% of the snakebites in Brazilian Amazonia for that period. The incidence rate was 0.123 cases/100, 000 inhabitants/year. The most affected group is that of working age men, suggesting occupational risk. Most of bites were on lower limbs. Pain, edema and paresthesia were the most common symptoms. Systemic symptoms not usually associated with coral snakes envenomings, such as coagulopathy and thrombocytopenia, have been reported in Amazonia. Five patients received less antivenom than indicated by the Health Ministry. Based on these results, we recommend the execution of educational programs to avoid such accidents and to teach both the general public and health professionals the correct treatment for the bites. We also suggest that the covering of Intensive Care Units in the region needs to be improved to avoid deaths. Highlights: Coral snake bites represent 0.05% of the snakebites reported in Brazilian Amazonia. Working age men was the most affected group, suggesting occupational risk. Pain, edema and paresthesia were the most common symptoms.